Drivers of the adoption of farmer-innovated sprinkler irrigation systems: evidence from Kalpitiya, Sri Lanka - Aheeyar, Mohamed M. M.; Manthrithilake, Herath; Pathmarajah, S. (2016)
Since the 1980s, along with many other countries, Sri Lanka rapidly embraced groundwater irrigation. At the same time, the government, externally funded projects and nongovernmental organizations (NGOs) made bold efforts to promote water-saving technologies, such as drip and sprinkler irrigation systems, among farmers, but achieved little or no success. Despite the continuous failure in the promotion of 'professionally designed', micro-irrigation systems across the country, grassroots innovations have emerged. These locally initiated endeavors, mainly in sprinkler irrigation, have been adopted comfortably and competently by the farmers themselves without any external assistance. Farmers in the Kalpitiya Peninsula have adopted this technology within a few years. This paper presents the 'drivers' behind this spontaneous 'irrigation revolution' that has occurred in the peninsula. The findings indicate that the adoption of sprinkler irrigation in this groundwater-based agricultural ecosystem has brought in tremendous changes to agricultural practices, and also to the lifestyles and livelihoods of the people living in the area. These positive and desirable results have been obtained with zero subsidy provision, and without any external inputs from the government or NGOs. Adoption of this sprinkler system for irrigation has increased the net sown area, net irrigated area and cropping intensity, resulting in significant economic returns and welfare gains. The low-cost sprinkler innovations are considered as an input cost that is recoverable within a year or two, rather than a long-term capital investment. The main drivers of this technological shift are (i) significant reduction in the cost of irrigation due to lower expenditure on labor and energy; (ii) user-friendly and affordable technology; (iii) easy to assemble, install and manage (operation and maintenance); (iv) easy access to components and spare parts (locally available); (v) potential to cultivate high-value cash crops; (vi) environmental context of the area (high number of rainless days, year-round availability of groundwater resources, low water-holding capacity of sandy soil); and (vii) immediate connection to markets through mobile phones and improved road networks. Promotion of micro-irrigation exclusively as a water-saving technology, as done in the past, is not a motive for farmers to adopt micro-irrigation systems. This is particularly the case where farmers do not recognize water scarcity as a 'real constraint'. Conserving water and sustainable management of the resource, at least for the time being, is not factored in farmers decision making.